ANALISIS PENERAPAN ANGGARAN PROYEK (STUDI KOMPARASI PADA PT. CEMPAKA NUSANTARA DAN PT. JONJORO PANRITA KAMPONG) - Nasrullah, Nasrullah (Pusat Penerbitan dan Publikasi Ilmiah Fakultas Ekonomi, Universitas Muslim Indonesia, 2018)
The role of management control over the object of research at PT. Cempaka Nusantara on the implementation of the project has a role to play in the effectiveness of the budget towards the realization of the project costs with a range of 26.28% while at PT. Jonjoro Panrita Kampong with a range of 54.21% with a time range between 2011-2015. The results of the study show that control is how management, especially project management, can control the use of components of raw material costs, labor, overhead and fixed costs, thus that the project can be completed by contributing to the company thus that this is expected to be profit.